A wet chemistry synthesis of silver nanoparticles from bulk material - Guimera Coll, Pablo (Kansas State University, 2015)
An easier, cheaper and scalable method to obtain silver nanoparticles, AgNPs, directly from the bulk material has been obtained. Two different solvents were tried, water and ethylene glycol, the coating agent was polyvinylpyrrolidone, PVP, and two different silver sizes were used, micron size powder and silver shots, millimeter size. It was seen that changing the size of bulk silver, the temperature of reaction, the amount of oxygen, the concentration of PVP and its molecular weight all had an important influence in the synthesis of nanoparticles. Different morphologies could be obtained when these parameters were adjusted ranging from spheres to triangles and hexagons. A complex mechanism is proposed: during the first step, bulk silver is oxidized by oxygen in solution, forming a thin layer of oxidized silver on the surface. Then, PVP acts as a reducing agent at the oxidized surface, where silver becomes Ag⁰ again. At the same time that PVP reduces the oxidized silver back to metallic silver; it coordinates with the silver atoms acting as a protecting agent. That coordination between PVP and silver pulls out the atoms and produces a detachment of silver atoms from the bulk surface. These silver-PVP complexes in solution later combine to form silver nanospheres and evolve to rods first and then triangles and hexagon with longer reaction time.
Keywords: Silver; Wet chemistry; Nanoparticles; Synthesis; Bulk